Effect of sildenafil citrate (Viagra) on the lipid profile of the normal and experimentally Induced Diabetic Male Rats - Al-Fartosi, Khalid G. (University of Thi-Qar Journal of Science, 2019)
The current study was designed to determine effectiveness of sildenafil citrate (viagra) on lipid profile of normaland experimentally induced diabetic male rats, the current study was carried out on (36) mature male mature rats, they were divided randomly into six equal groups, 6 of each group. The first group was administrated orally with (0.2 ml) of normal physiological saline (0.9% Nacl), the second group was injected (IP) by (0.5 ml/animal) with alloxane (125 mg.kg-1) , the third and fourth groups were administrated orally with viagra at doses (4 and 8 mg.kg-1), respectively, while the fifth and sixth groups injected (0.5 ml/animal) with alloxane (125 mg.kg-1), after one week, the (fifth and sixth) group were administrated orally with viagra at doses (4 and 8 mg.kg-1), respectively. The experiment was continued for 21 days. At the end of the experimental period, the animals were sacrificed, the blood samples were collected and the serum concentration of total cholesterol (T.C.), triglycerides (T.G.), high density lipoprotein (HDL), low density lipoprotein (LDL), very low density lipoprotein (VLDL) and atherogenic index were determined in the serum. The results showed a significant increase in the serum level of T.C., T.G., LDL, VLDL and atherogenic index to the normal and diabetic rats treated with viagra and decrease in HDL concentration of the normal and diabetic rats administered with viagra when compared this two groups with control and diabetic groups respectively.